2013
DOI: 10.1039/c3cp00040k
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous vibrational relaxation of carbon monoxide

Abstract: The first results relating to heterogeneous vibrational relaxation of carbon monoxide in an Al2O3 ceramics tube are reported, together with an estimation of its probability. It was found that the probability of heterogeneous relaxation εv of the first-excited state of CO on the Al2O3 surface lies in the range (5 to 7) × 10(-2). The measurements show that the probabilities of heterogeneous relaxation of CO(X(1)Σ, v) do not depend on the value of v, at least for v = 1, 2 and 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Following [20] and due to the lack of experimental data, we chose as default value of deactivation probability, γ v , for any mode of CO 2 being deactivated to the ground state, γ v (CO 2 (v > 0)) = 0.2, for a Pyrex surface (average value from table 1 of [63]). We use a constant value of 4 × 10 −2 for the deactivation probability for all levels of CO [63], which is significantly lower than for CO 2 , as measurements showed that the probabilities of heterogeneous relaxation of CO do not depend on the value of v, at least for v = 1, 2 and 3 [64]. A certain dependence on the vibrational level could be expected, similar to the case of N 2 , where a linear dependence of γ v with the vibrational level is reported [65,66].…”
Section: Vibrational Quenching On the Wallmentioning
confidence: 99%
“…Following [20] and due to the lack of experimental data, we chose as default value of deactivation probability, γ v , for any mode of CO 2 being deactivated to the ground state, γ v (CO 2 (v > 0)) = 0.2, for a Pyrex surface (average value from table 1 of [63]). We use a constant value of 4 × 10 −2 for the deactivation probability for all levels of CO [63], which is significantly lower than for CO 2 , as measurements showed that the probabilities of heterogeneous relaxation of CO do not depend on the value of v, at least for v = 1, 2 and 3 [64]. A certain dependence on the vibrational level could be expected, similar to the case of N 2 , where a linear dependence of γ v with the vibrational level is reported [65,66].…”
Section: Vibrational Quenching On the Wallmentioning
confidence: 99%